Pendampingan Pelatihan Kesenian Hadroh pada Grup Shalawat An-Najah Kelurahan Cawang Jakarta Timur: Pengabdian - Ifham Choli; Sutiono; Syarifah Soraya; Taufik Hidayat (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This community service activity is carried out by providing art materials, related to hadroh art instruments for the women of the An-Najah shalawat group and the community around Cawang sub-district, Kramat Jati district, East Jakarta. In this service, it is specifically for mothers who live around RW 010, Cawang sub-district, Kramat Jati district, East Jakarta. This service activity is a form of implementing the tri dharma of higher education. The method of implementing this service is carried out by tutorials delivering materials related to the problem of makhraj for shalawat, how to hold and hit hadroh art instruments, such as explaining how to hit the tambourine, bass, octagon and others directly by the service participants. The time for implementing this service is in the even semester of 2024/2025 as many as one meeting a week, precisely every Friday, from February to July 2024. The place for implementing the service is at Majlis Ta'lim Nurul Qur'an Jl. Ja'ani Nasir, RT 001/010, Cawang sub-district, Kramat Jati district, East Jakarta. The results of this community service show that the hadroh arts learning helped mothers understand how to properly strike the hadroh instruments in the Cawang sub-district area, making the participants confident in performing hadroh accompanying shalawat. The community service participants learned how to strike with the correct tone and rhythm, and so on.